Evaluation of Content Validity for an Educational Media Instrument to Enhance Early Childhood Education (PAUD) Teachers’ Nutrition Knowledge - Salsa Belladinna Putri Utami; Nur Riska; Rusilanti Rusilanti; Agung Gumelar (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
This study aims to evaluate the content validity of an educational media instrument developed to measure the quality of educational magazine media designed to enhance Early Childhood Education (PAUD) teachers’ knowledge of nutrition. Evaluating educational media instruments is crucial to ensure that the materials used in teacher professional development are relevant, accurate, and clear. Without a well-validated instrument, there is a risk that the media applied in educational settings may not effectively achieve its intended learning outcomes. A descriptive quantitative research design was employed, with expert judgment serving as the central approach for validation. Several specialists in the fields of education and instrument development were involved in evaluating the instrument. Their assessment focused on three main aspects: media design, language clarity, and content relevance related to nutrition education. The findings indicate that the instrument achieved strong content validity across all domains, demonstrating its potential to accurately assess the feasibility and quality of nutrition education media. The study contributes to the field of educational evaluation by highlighting the critical role of content validity in the development of instruments intended to support teacher professional learning and the improvement of instructional materials.